PENGARUH RESIKO BISNIS, UKURAN PERUSAHAAN, DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR DI BEI: (Studi Pada Perusahaan Sub Sektor Otomotif Dan Komponen Periode 2016-2020) - Rina Puspitasari; Erwin Syahputra; Iing Sri Hardiningrum (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
The aim of this research is to determine the influence of business risk, company size and sales growth on the capital structure of automotive sector companies listed on the Indonesian Stock Exchange. It is hoped that this research can contribute to the development of financial management science, and as input for company leadership in making decisions related to business risk, company size and sales growth. The population in this research is the financial reports of automotive companies listed on the IDX for the 2016-2020 period. This research uses data analysis, namely panel data regression analysis which is used to statistically test the hypothesis model, as well as the extent to which the proposed capital is consistent with the data sample. The results of this research show that business risk has a positive and significant effect on the capital structure of automotive sector companies listed on the IDX. Company size and sales growth have a negative and insignificant effect on the capital structure of automotive sector companies listed on the Indonesia Stock Exchange.